A global call to action: strengthening strategies to combat dysglycemia and improve public health outcomes - Hirani, Krish; Sundheim, Brody; Blaschke, Mateo; Lemos, Joana R. N.; Mittal, Rahul (Frontiers in Public Health, 2025)
Dysglycemia, affecting over 800 million people globally, poses a significant challenge to health systems and economies, contributing to healthcare costs exceeding 966 billion annually. This practice paper presents a strategic, multi-level framework addressing dysglycemia through evidence-based interventions. Effective measures include promoting low-glycemic diets, structured physical activity, and continuous glucose monitoring technologies to enhance self-management. Policy initiatives such as sugar taxation and healthy food subsidies incentivize healthier choices, while healthcare provider training enhances clinical capacity. These integrated efforts have demonstrated reduced hospitalizations, improved cognitive function and economic benefits through lower medication costs and enhanced workforce productivity. Addressing healthcare inequities and tailoring interventions to cultural contexts are critical to long-term success.